2004
DOI: 10.1002/ajmg.a.30258
|View full text |Cite
|
Sign up to set email alerts
|

45,X/47,XXX/47,XX, del(Y)(p?)/46,XX mosaicism causing true hermaphroditism

Abstract: Sex differentiation in humans depends on the presence of the Y-linked gene SRY, which is activated in the pre-Sertoli cells of the developing gonadal primordium to trigger testicular differentiation. Occasionally testicular formation can take place in subjects lacking a Y chromosome resulting in a 46,XX sex reversal condition. True hermaphroditism (TH) is a rare form of intersexuality characterized by the presence of testicular and ovarian tissue in the same individual. Genetic heterogeneity has been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…OTDSD is defined as the presence of ovarian tissue containing follicles along with testicular tissue either in the same gonad (ovotestis) or in the opposite gonad, the most common type being unilateral ovotestis with contralateral ovary/testis (50%) followed by bilateral ovotestis (30%) (Achermann & Hughes, ). Mosaicism, chimerism and single gene mutations are most commonly responsible for development of OTDSD (Nieto et al ., ). SRY (Y‐chromosome) is found in around 40% of OTDSD and in about 10% of 46,XX OTDSD (Berkovitz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…OTDSD is defined as the presence of ovarian tissue containing follicles along with testicular tissue either in the same gonad (ovotestis) or in the opposite gonad, the most common type being unilateral ovotestis with contralateral ovary/testis (50%) followed by bilateral ovotestis (30%) (Achermann & Hughes, ). Mosaicism, chimerism and single gene mutations are most commonly responsible for development of OTDSD (Nieto et al ., ). SRY (Y‐chromosome) is found in around 40% of OTDSD and in about 10% of 46,XX OTDSD (Berkovitz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…To date, karyotype analyses, molecular cytogenetic and DNA analyses have been performed on the blood, skin and gonadal tissues to determine the mechanism for different karyotype observed in a patient with an OTDSD. As a result of these studies, mosaicism, tetragametic chimerism or a single gene mutation have been found as the cause of this rare and complex disorder (Nieto et al. , 2004; Alonso et al.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of OTDSD patients with a male sex assignment begin to experience feminisation including breast development and cyclic haematuria (Walker et al. , 2000; Wiersma, 2001; Nieto et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SRY translocation is responsible for 10% of all 46,XX female to male sex reversal. 12 Formation of ovotestes, where ovarian and testicular tissues coexist in the same organ, can also occur in cases of ectopic SRY activity. 13,14 SRY is a transcription factor with a DNA-binding high-mobility group box domain.…”
Section: Sry and The Beginnings Of Malenessmentioning
confidence: 98%